PERAN WORLD TRADE ORGANIZATION (WTO) DALAM PENYELESAIAN SENGKETA PERDAGANGAN TERHADAP EKSPOR APEL SELANDIA BARU-AUSTRALIA TAHUN 2007 - Rahatesa, Queenta; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
World Trade Organization (WTO) is an International organization that specializes in trade between countries. In 2007, the Australian government had stopped importing New Zealand apples because they had some harmful bacteria there upon New Zealand reported it to the WTO organization.The method used in this research is qualitative research. The data obtained comes from books, journals, theses, documents, articles, internet sites and other sources related to this research. The research accentuation is how the mechanism WTO resolving the trade disputes of New Zealand’s apples. This study using the perspective of neoliberalism by Tom Paine, Clive Archer’s theory of international organizations and also using group level analysis.Many procedures that New Zeland proposed has been issued to WTO in hope to allow New Zealand’s apples to reenter Australia. The settlement lasted for approximately 4 years under the supervision of the Dispute Settlement Body (DSB). On examination of Appellate Body didn’t found fire blight, European cancer and apple leafcurling midge (ALCM) in New Zealand apples. This, New Zeland won over the issue and Australia ready to give an entrance for New Zeland apples after 8 months of break time.Keywords: Perspektif of Neoliberalism, Theory of International Organizations, Dispute Settlement Body.